Newly identified APN splice isoforms suggest novel splicing mechanisms may underlie circRNA circularization in moth. Issue 9 (26th July 2019) - Gao, Meijing; Liu, Yuan; Wang, Yun; Zhang, Xiao; Dong, Sa; Liu, Xianjin
Abstract : Circular RNA (circRNA) have long been considered by‐products of splicing errors, but the coordination of RNA transcription and exon circularization events remains poorly understood. Here, we investigated this question using genes encoding aminopeptidases N (APNs), which are receptors of Bacillus thuringiensis toxins, in the cotton bollworm, Helicoverpa armigera . We cloned and sequenced the cDNA of ten APN genes ( HaAPN1‐10 ) located in the same APN gene cluster, and detected 20 and 14 novel splicing isoforms with exon skipping in HaAPN1 and HaAPN3, respectively, whereas no or very few variants were found in the remaining genes. Further study identified 14 and 6 circular RNA (circRNA) in HaAPN1 and HaAPN3, respectively. Neither novel splicing isoforms nor circRNA were detected in HaAPN2 and HaAPN5 . Distinct from the conventional GT/AG splicing signal, short co‐directional repeats were involved in the splicing of the linear and circular isoforms of HaAPN1 and HaAPN3 . Identification of the splice sites revealed that the linear isoforms may be related in some way to the circularization. Moreover, phylogenetic analysis and detection of circRNA of the APN gene of the diamondback moth, Plutella xylostella ( PxAPN3 ), showed that circRNA formation is relatively conserved during the lepidopteran evolutionary process. These results contribute to an improved understanding of lepidopteran APNs and this novel class of insect circRNA. Abstract : We demonstrate that linear and circular splice transcripts are common in certain aminopeptidase N (APN) genes. We screened ten HaAPNs located in the same cluster of the genome and demonstrated that linear and circular splice transcripts are common in these APNs, and that circRNAs are related in some way to linear spliced events. A class of noncanonical splicing signals (short co‐directional repeats) was shown to participate in the formation of the two types of transcripts.